Association Between Allergic Conditions and Celiac Disease in Pediatric Patients - Cabrera, Carmen M. (Turkish Journal of Gastroenterology, 2022)
Cite this article as: Cabrera CM. Association between allergic conditions and celiac disease in pediatric patients. Turk J Gastroenterol. 2022;33(7):625-626.